Descriptive Epidemiology and Outcomes of Patients with Short Stay Hospitalizations for the Treatment of Congestive Heart Failure in the US - Zilberberg MD; Nathanson BH; Sulham K; Mohr JF; Goodwin MM; Shorr AF (Dove Medical Press, 2023)
Marya D Zilberberg,1 Brian H Nathanson,2 Katherine Sulham,3 John F Mohr,3 Matthew M Goodwin,3 Andrew F Shorr4 1EviMed Research Group, LLC, Goshen, MA, USA; 2Optistatim, LLC, Longmeadow, MA, USA; 3scPharmaceuticals, Burlington, MA, USA; 4Washington Hospital Center, Washington, DC, USACorrespondence: Marya D Zilberberg, EviMed Research Group, LLC, PO Box 303, Goshen, MA, 01032, USA, Email evimedgroup@gmail.comBackground: Congestive heart failure (CHF) hospitalizations cost the US $35 billion annually. Two-thirds of these admissions, generally requiring /=65 years: 68.3% vs 71.9%), less likely covered by Medicare (71.9% vs 75.4%), and had a lower comorbidity burden (Charlson: 3.9 [2.1] vs 4.5 [2.2) than patients with LLOS; they less frequently developed acute kidney injury (0.4% vs 2.9%) or a need for mechanical ventilation (0.7% vs 2.8%). A higher proportion with SLOS than with LLOS underwent no procedures (70.4% vs 48.4%). Mean LOS (2.2 [0.8] vs 7.7 [6.5]), direct hospital costs ($6150 [$4413]) vs $17,127 [$26,936]), and aggregate annual hospital costs $3,131,560,372 vs $11,359,002,072) were all lower with SLOS than LLOS. All comparisons reached alpha = 0.001.Conclusion: Among patients admitted for CHF, nearly ½ have LOS